Loading web-font TeX/Main/Regular

5(7-2h)+2=27

Simple and best practice solution for 5(7-2h)+2=27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(7-2h)+2=27 equation:



5(7-2h)+2=27
We move all terms to the left:
5(7-2h)+2-(27)=0
We add all the numbers together, and all the variables
5(-2h+7)+2-27=0
We add all the numbers together, and all the variables
5(-2h+7)-25=0
We multiply parentheses
-10h+35-25=0
We add all the numbers together, and all the variables
-10h+10=0
We move all terms containing h to the left, all other terms to the right
-10h=-10
h=-10/-10
h=1

See similar equations:

| x+(4x-4)+(6x-3)=180 | | -(-2y+1)=2y-1 | | 9a-4+3(a-11=23 | | 100/60=(4/5)/x | | 23x=23,000 | | 13x+2=100 | | 2+4(6-2x)=8 | | 0.75x=63.75 | | 2x+85+5x+29=93 | | 13m=300 | | 4(3b+7)=88 | | 1.6^(x-4)=5^(3x) | | -2(7z-4)=50 | | 4(7-6k)=-28 | | -2/1j=7/8 | | 2x^2+31x-7.9=0 | | 6.3a+15=90.6 | | -3(4n-5)=24 | | 3(6+5w)=18 | | (2/1)x+13=9 | | 2x-11=x-15=2x-72 | | 20/100=x/75 | | 0=16t^2+8 | | 2x-x=48 | | 8=9m-4m=3 | | -26p-6(5-6p)=6(p-5)-32 | | 2(-3+6z)=42 | | x=0.18x+24.41 | | x=0.18x+24.41 | | 2/5=y+4/3y | | 4x÷7=3 | | -1.5+k=8.2k=8.2+(-1.5)k=6.7 |

Equations solver categories